ANALISIS HUBUNGAN ANTARA PENGETAHUAN KARYAWAN TENTANG K3 DENGAN TINGKAT KECELAKAAN KERJA DI PT ARGO PANTES - Widya Chandra; Fini Fajrini (Jurnal Riset Multidisiplin Edukasi, 2025)
The rate of workplace accidents in the textile industry, particularly at PT Argo Pantes, has shown a significant increase, with 6 cases in one year, predominantly involving chemical exposure. Low Occupational Health and Safety (OHS) knowledge is one of the main contributing factors. This study aims to analyze the relationship between employees' OHS knowledge (covering cognitive, affective, and psychomotor aspects) and workplace accident rates, as well as the influence of age and work tenure.  The study used a cross-sectional design with a quantitative approach. The sample consisted of 60 employees from the KAI Unit of PT Argo Pantes, selected through total sampling. Data were collected using an OHS knowledge questionnaire and secondary data from workplace accident reports. Data analysis was performed using Pearson correlation, t-test, and ANOVA. There was a significant negative correlation between OHS knowledge and workplace accidents (r = -0.394; p = 0.002). About 60% of employees had low OHS knowledge, and the age group ≤35 years was more prone to accidents (p = 0.047). Work tenure did not have a significant effect (p = 0.053).  Improving OHS knowledge through multidimensional training can reduce the risk of workplace accidents, especially among younger employees. The company should develop simulation-based OHS training programs and strengthen supervision of Personal Protective Equipment (PPE) usage in high-risk areas.